PARTICIPATORY ACTION RESEARCH ON THE HEALTH AND WELL-BEING BENEFITS OF COMMUNITY GARDENING: A STUDY OF RESIDENTS IN AN ISLAMIC ELDERLY HOME - Nordin, Nikmatul Adha; Zainol, Rosilawati; Ahmad, Faizah; Awang, Siti Nor; Razali, Atikah (PLANNING MALAYSIA, 2022)
This study employs a Participatory Action Research (PAR) approach in finding practical solutions to promote sustainable active ageing living environment for the elderly in a Muslim based elderly home – the Baitul Maab, Temerloh. The study was conducted in three sequential phases: initialization, action and reflection utilizing multiple data collection methods which included visual assessment, Focus Group Discussion, collaborative mapping and survey. During the Focus Group Discussion, several proposals were put forward by the residents. One of the proposals by the FGD participants were to have a community garden as an outlet for the residents to engage in healthy activities collectively. Based on this, a community garden called Laman Herba and Sayuran was then created by the researchers and the residents through gotong royong activities. A survey was carried out a year later to determine the usage of the garden and how it helped the community in achieving a healthy lifestyle. The findings suggest that the community garden is perceived to be able to help the residents to be healthier and that it improved their well-being. The study also suggested that elderly below 65 years old were in the age group who most benefited from having a community garden as they still have the energy and strength to do gardening activities This study concludes that community gardening is perceived to yield many benefits to elderly’s health and social well-being. However, for the garden to be efficient, it has to be equipped with the necessary infrastructure such as stools as resting place and easy-to-reach water supply.